Ekologi Politik Pencemaran Air: Hegemoni Industri Ekstraktif dan Marginalisasi Petani di Bojonegoro - Ahmad Sholikin (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2018)
The massive expansion of the oil and gas extractive industry in Bojonegoro Regency, Indonesia, has triggered severe hydrological disruptions, jeopardizing the socio-ecological foundation of local agrarian communities. While previous studies have predominantly focused on land conflicts and revenue-sharing dynamics, this research shifts the analytical paradigm toward hydropolitics. This study aims to unpack the political ecology of water pollution, corporate hegemony, and the systemic marginalization of local farmers in the region. Employing a critical qualitative approach through an instrumental case study method, data were gathered via in-depth interviews, participant observation, and document analysis in the "Ring 1" operational areas. The findings reveal four crucial realities. First, water pollution in the area is not merely a technical accident but a legitimized 'political compromise' stemming from systemic environmental governance failures and the weakening of regulatory instruments. Second, the extractive industry, in alliance with local elites, utilizes development narratives and manipulates Corporate Social Responsibility (CSR) programs as a social pacifier and greenwashing strategy to suppress grassroots conflicts. Third, this ecological degradation leads to the systemic marginalization of the agrarian class, manifesting as a 'resource curse' that devastates their economic resilience and food sovereignty, forcing a massive proletarianization. Finally, in response to this structural oppression, an organic hydropolitical resistance has emerged at the grassroots level—significantly driven by rural women—demanding spatial justice and the restoration of their ecological rights. This article concludes that resolving such ecological crises requires dismantling the extractive hegemony and institutionalizing a legally binding 'nexus safeguard mechanism' that prioritizes the constitutional right to water and food over the accumulation of energy capital.